Identification, Assessment and Raking of Geomorphosites: A Guide to Sustainable Tourism Development. Case Study of Khorramabad County in Iran - MAGHSOUDI, Mehran; DEHESTANI, Hedieh; BAHARVAND, Mehdi; HAJIKARIMI, Zahra (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019, 2019)
Geotourism is defined as tourism that involves protection of geographical features, environment, culture, aesthetic and heritage of the places that are visited and bring prosperity to its citizens. the importance of geomorphosites in tourism sustainable development, different researches have been done around the world in recent decades Khorramabad county is located in Lorestan province in the southwestern Iran. It has a high potential to attract domestic and foreign tourists owing to its geographical location, climate, topography and geological specific conditions. In this paper, 39 sites were also studied using field observations and available information, and then 8 sites were chosen and ranked using Rocha model (2014), fieldwork and experts' viewpoint and researches of this study. Finally, assessment of 8 geomorphosites was done using a suitable model for the study area. According to the assessment of 8 geomorphosites, Makhmalkooh was selected with high score and Salt mines have earned the lowest score. Also, the results showed that most of the selected geomorphosites have good infrastructure and are approximately near to the urban settlement.